Globalization, Jobs, and Welfare: The Roles of Social Protection and Redistribution - Priya Ranjan (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper studies the welfare and policy implications of globalization when risk averse workers face the risk of unemployment. If the jobs performed by domestic workers can be easily substituted by imports, then globalization reduces wages and increases unemployment. In this situation, in the absence of any government intervention globalization not only reduces the welfare of workers but could reduce social welfare as well. Both unemployment benefits and severance payments can protect workers against labor income risk, but the latter enhances welfare more if job destruction is the source of unemployment. When optimal redistribution and social protection policies are in place, globalization necessarily improves social welfare.
Keywords: F16; F66; F68; 330; offshoring; unemployment; endogenous job destruction; severance payments; unemployment benefits